Quality of reporting in abstracts of clinical trials using physical activity interventions: a cross-sectional analysis using the CONSORT for Abstracts - Angélica Trevisan De Nardi; Leony Morgana Galliano; Nórton Luís Oliveira; Daniel Umpierre (Journal of Evidence-Based Healthcare, 2023)
BACKGROUND: The quality of reporting in the abstract section of scientific articles is one of the important aspects of good communication of trials. OBJECTIVES: We investigated abstracts of randomized clinical trials (RCTs) in the physical activity field according to adherence to the Consolidated Standards of Reporting Trials (CONSORT) for Abstracts (primary outcome) and checked the recommendations of the selected journals regarding the contents and structure of the abstract. METHODS: This study is a descriptive, cross-sectional study of the Strengthening the Evidence in Exercise Sciences (SEES) Initiative. RCTs published in 9 exercise science journals and 2 general medicine journals during 2019 were eligible. Two researchers conducted study selection and, thereafter, assessment of the abstracts using a form comprising 16 items based on CONSORT for Abstracts. Also, extracted, in duplicate and independently, the journals’ recommendations for authors. RESULTS: 131 abstracts were eligible for evaluation. From items evaluated, those with the highest adherence were objectives or hypothesis (99%), conclusion (98%), and intervention (94%). The lowest reporting was observed in the number of participants analyzed (6%), allocation and randomization (1%), and funding (1%). Ten journals recommended the abstract structure, but only two mentioned the CONSORT for Abstracts. CONCLUSIONS: There is variable and suboptimal adherence to the CONSORT for Abstracts in trials in the physical activity field and poor recommendation of this instrument in journals selected. Therefore, we suggest editors, reviewers, and authors a greater adherence to guidelines, and to journal recommendations to improve the quality of reporting of abstracts in the physical activity field.